Bukti Validitas dan Penerapan Structured Oral Case Analysis (SOCA) pada Pendidikan Kedokteran di Indonesia: Sebuah Tinjauan Literatur - Priska, Yoana (Syntax Literate, 2026)
Developing core clinical reasoning skills is a mandatory educational goal for all medical students. The Structured Oral Case Analysis (SOCA) is widely utilized as an assessment method for evaluating these competencies. This study sought to systematically examine the local application and psychometric support for SOCA within Indonesian medical programs. A comprehensive literature review was conducted covering publications from 2015 to 2025, utilizing relevant English and Indonesian search terms across various academic databases. Articles were subsequently systematically screened based on predefined inclusion and exclusion criteria through a review of titles and abstracts. The analysis revealed three central themes: assessment terminology, execution practices, and evidence of validation for the SOCA method. Notably, terminological inconsistencies were found across Indonesian institutions despite standardized methods. Furthermore, documentation regarding implementation practices primarily details time allocation and assessment rubrics. While evidence supports concurrent validity, content validity, and inter-rater reliability, this validation is restricted to the module assessment level. Crucially, validation for SOCA in a high-stakes assessment context is currently absent from the literature. In summary, the current psychometric profile confirms that SOCA is a valid and reliable tool for low-stakes assessment applications within Indonesian medical education.